Puja Mandala sebagai Manifestasi Toleransi dan Pluralisme: Perspektif Teologi dan Sosial di Bali - Febrian Arif Pratama Febrian (Sociale : Journal of Social and Political Sciences, 2026)
This study explores the concept of Puja Mandala as a symbol of religious harmony in Bali, Indonesia, where various religions coexist. The study highlights the importance of Puja Mandala, which includes five different places of worship in one area, as a manifestation of multiculturalism and pluralism. The analysis uses indicators of religious harmony, such as tolerance, equality, and collaboration, to assess the dynamics within Puja Mandala. This study refers to a framework developed by the Indonesian Ministry of Religious Affairs in 2017, which provides a theoretical basis for understanding the coexistence of various religious groups in Bali. Despite the challenges posed by radical ideologies and the potential for conflict between majority and minority groups, this study analyzes the theoretical framework of religious harmony in Bali, which reflects the diversity of religious groups, as depicted in Puja Mandala. Based on a literature review, this study discusses how Balinese society has managed to maintain peaceful coexistence despite facing challenges from radical ideologies and divisive forces. In addition, this study acknowledges the ongoing threats to tolerance, including apathy and the domination of certain groups over others, which can lead to social fragmentation. However, it argues that Puja Mandala serves as a beacon of hope, illustrating that with a commitment to tolerance and understanding, communities can overcome these challenges and maintain harmony. In conclusion, Puja Mandala is not only a religious site but a vital symbol of interfaith harmony in Bali. This study underscores the importance of preserving and promoting the values of tolerance and cooperation, which are essential for maintaining peace in a diverse society.